1, 3, 5‐Trihydroxy‐13, 13‐dimethyl‐2H‐pyran [7, 6‐b] xanthone directly targets heat shock protein 27 in hepatocellular carcinoma. (30th October 2013) - Fu, Wei‐ming; Wang, Wei‐mao; Wang, Hua; Zhu, Xiao; Liang, Yan; Kung, Hsiang‐fu; Zhang, Jin‐fang
Abstract We previously showed that the small molecule 1, 3, 5‐trihydroxy‐13, 13‐dimethyl‐2H‐pyran [7, 6‐b] xanthone (TDP) induces apoptosis in hepatocellular carcinoma (HCC) by suppressing Hsp27 expression, although the mechanism is not fully understood. To investigate the functional association between TDP and Hsp27 protein in HCC, recombinant Hsp27 protein was incubated with TDP at room temperature, and assayed by mass spectrum (MS) and natural electrophoresis. TDP effectively stimulated Hsp27 to form aggregates ex vitro, leading to suppression of its chaperone activity. The aggregates were degraded by the ubiquitin–proteasome (UPS) pathway. TDP directly interacted with Asp17 and Phe55 in chain C of Hsp27 on the basis of bioinformatic prediction. In conclusion, Hsp27 is a direct target of TDP in its anti‐cancer activity, which provides strong support for a clinical application.